2012
DOI: 10.1186/1471-2393-12-88
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of childbirth-related post-traumatic stress symptoms

Abstract: BackgroundThere is evidence that traumatic birth experiences are associated with psychological impairments. This study aimed to estimate the prevalence of childbirth-related post-traumatic stress symptoms and its obstetric and perinatal risk factors among a sample of Iranian women.MethodsThis was a cross-sectional study carried out in Bushehr, Iran during a 3-months period from July to September 2009. Data were collected from all women attending eleven healthcare centers for postnatal care 6 to 8 weeks after c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
116
3
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 28 publications
10
116
3
6
Order By: Relevance
“…Psychosocial variables included elevated symptoms of depression at 32 weeks of pregnancy (Myers et al 2013; O'Hara and McCabe 2013) (EPDS ≥13); elevated anxiety symptoms at 32 weeks of pregnancy (Heron et al 2004) (CCEI ≥9); history of alcoholism or drug addiction (Bystrova et al 2009) (recent, past, never); smoking in pregnancy (Myers et al 2013) (yes vs. no); self-reported history of a psychiatric diagnosis (Myers et al 2013; O'Hara and McCabe 2013) (yes vs. no); level of social network (Myers et al 2013; O'Hara and McCabe 2013) measured by scoring quantitative measures of connectedness with friends and family using the median value cutoff (<24 vs. ≥24) (Weisman et al 2010); stressful life events in childhood using the median value cutoff (Golding et al 2009) (>3 events vs. 0–3 events); and recent stressful life events at 18 weeks of pregnancy using the median value cutoff (Golding et al 2009; O'Hara and McCabe 2013) (>3 events vs. 0–3 events). We also examined potential covariates related to reproductive and medical health including parity (Myers et al 2013) (0 vs. ≥1), consumption in pregnancy of fish high in omega-3 (Golding et al 2009) (yes vs. no), and method of infant feeding (Dennis and McQueen 2009) (not exclusive vs. exclusive breastfeeding) during the first month after birth for symptoms of depression and anxiety at 2 months and during the first 6 months after birth for symptoms of depression and anxiety at 8 months (Modarres et al 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Psychosocial variables included elevated symptoms of depression at 32 weeks of pregnancy (Myers et al 2013; O'Hara and McCabe 2013) (EPDS ≥13); elevated anxiety symptoms at 32 weeks of pregnancy (Heron et al 2004) (CCEI ≥9); history of alcoholism or drug addiction (Bystrova et al 2009) (recent, past, never); smoking in pregnancy (Myers et al 2013) (yes vs. no); self-reported history of a psychiatric diagnosis (Myers et al 2013; O'Hara and McCabe 2013) (yes vs. no); level of social network (Myers et al 2013; O'Hara and McCabe 2013) measured by scoring quantitative measures of connectedness with friends and family using the median value cutoff (<24 vs. ≥24) (Weisman et al 2010); stressful life events in childhood using the median value cutoff (Golding et al 2009) (>3 events vs. 0–3 events); and recent stressful life events at 18 weeks of pregnancy using the median value cutoff (Golding et al 2009; O'Hara and McCabe 2013) (>3 events vs. 0–3 events). We also examined potential covariates related to reproductive and medical health including parity (Myers et al 2013) (0 vs. ≥1), consumption in pregnancy of fish high in omega-3 (Golding et al 2009) (yes vs. no), and method of infant feeding (Dennis and McQueen 2009) (not exclusive vs. exclusive breastfeeding) during the first month after birth for symptoms of depression and anxiety at 2 months and during the first 6 months after birth for symptoms of depression and anxiety at 8 months (Modarres et al 2012). …”
Section: Methodsmentioning
confidence: 99%
“…In other words, the longer the duration of the adverse event is, the lower the PTC becomes. In a study by Modarres et al, PTC and post stress disorders were found to be high in those who had trauma stories in the past [12]. It is of great importance that such women become pregnant after the traumas are healed as it is important for maternal and newborn health [16].…”
Section: Discussionmentioning
confidence: 99%
“…A perception of traumatic childbirth (PTC) can occur not only in individuals with birth experience but also in those at different times of life, such as childhood and adolescence [11,12]. When it is evaluated according to life periods and gender in details, it is observed that a perception of traumatic childbirth is most often seen in women at the age of reproduction [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, traumatic delivery experiences are thought to increase risk for postpartum PTSD (Ayers and Pickering 2001; Modarres et al 2012; O'Donovan et al 2014). Table II and Fig.…”
Section: Introductionmentioning
confidence: 99%